Handbook of research on gaming trends in P-12 education - Russell, Donna 1955-; Laffey, James M. 1949- (Advances in Game-Based Learning (AGBL) Book Series, 2016)
"This book provides current research intended to aid educators, school administrators, and game developers in teaching today's youth in a technology-immersive society, melding gaming for entertainment purposes as well as gaming applied within educational settings with an emphasis on P-12 classrooms"...